Investigating potential targets of Wulingsan in diabetic nephropathy through network pharmacology and experimental validation - Xicheng Hu; Zhen Wang; Liyan Zhang (Frontiers in Molecular Biosciences, 2025)
BackgroundDiabetic Nephropathy (DN), a major microvascular complication of diabetes, poses challenges for current treatments to effectively delay its progression. Wulingsan (WLS), a traditional Chinese medicine formula, possesses potential for regulating water-fluid metabolism, and exhibits anti-inflammatory and antioxidant properties, yet its multi-target mechanism in treating DN remains unclear. This study aims to systematically elucidate the molecular mechanisms of WLS in the treatment of DN through network pharmacology, molecular docking, and in vitro experiments.MethodsActive ingredients of WLS and their targets were screened using the TCMSP database, while DN-related targets were obtained from the GeneCards and OMIM databases to construct an “ingredient-target-disease” network. GO and KEGG pathway enrichment analyses were performed using DAVID to identify key biological processes and signaling pathways. A protein-protein interaction (PPI) network was constructed via the STRING database, and key targets were screened using the CytoHubba plugin. Subsequently, molecular docking and molecular dynamics simulations were conducted to validate the binding affinity and stability of active ingredients with key targets. In vitro, a high glucose-induced HK-2 cell model was employed, and the effects of WLS on cell viability and cell cycle were assessed using CCK-8 assays and flow cytometry, respectively.ResultsThe study screened and identified SRC, AKT1, TNF, ESR1, and HSP90AA1 as key targets for the treatment of DN. KEGG enrichment analysis revealed that WLS primarily regulates signaling pathways such as PI3K-Akt and MAPK, which are closely associated with inflammation, oxidative stress, and fibrosis. Molecular docking indicated that active ingredients (β-caryophyllene, alisol C) exhibited binding energies below −5.0 kcal/mol with key targets (TNF, HSP90AA1), and molecular dynamics simulations further validated their binding stability. In vitro experiments demonstrated that WLS significantly inhibited the proliferation of high glucose-induced HK-2 cells (P < 0.01) and induced G2/M phase cell cycle arrest (P < 0.01).ConclusionWulingsan alleviates the progression of Diabetic Nephropathy by its multiple active ingredients acting synergistically on key targets such as SRC, AKT1, and TNF, thereby regulating PI3K-Akt and MAPK signaling pathways to inhibit inflammation, oxidative stress, and fibrosis. This research provides a theoretical basis for the clinical application of WLS, and its therapeutic efficacy warrants further verification through future in vivo experiments.